Foreign experience of CEO and corporate social responsibility: Evidence from China - Zhang, Yuyang; Dong, Liping (Frontiers in Environmental Science, 2023)
Foreign experience is a mechanism through which personal cognitions can be shaped into idiosyncratic characteristics. Under the unique institutional background of China, the purpose of this paper is to examine whether CEOs’ foreign experience will affect the performance of CSR and whether the influences of CEOs’ foreign experience on CSR vary from the categories of foreign experience or from the governance environments. We find that firms with returnee CEOs show better CSR performance. Moreover, the longer the CEO’s foreign experience, the better is the CSR performance. Our results are robust to endogeneity concerns, inclusion of additional control, and alternative measures of key variables. Further analyses indicate that foreign working and integrated experiences have important impacts on CSR performance; and the positive effect of foreign experience on CSR is more pronounced for firms located in better legal environment and for those audited by reputable auditor. Our findings highlight foreign experience of CEO as an important driver of CSR performance.